Draft genome sequence of lactobacillus plantarum CRL681, isolated from argentinean artisanal fermented sausages - Fadda, Silvina G. (2019)
Lactobacillus plantarum CRL681 was isolated from Argentinean artisanalfermented sausages. Here, the draft genome sequence of the CRL681 strain is described. The reads were assembled into contigs with a total estimated size of3,370,224 bp. A total of 3,300 open reading frames (ORFs) were predicted, including 3,126 protein-coding sequences. The draft genome sequence of L. plantarum CRL681 will be useful for understanding the organism?s metabolic activities and for biotechnological applications.